Olahraga Sehat (Jalan Santai) - Defri, Prayoga; martiani, Mariani (Jurnal Gotong Royong, 2024)
This report aims to foster the spirit of healthy sports (leisurely walks) in the Pangkalan Village Community. The implementation time of this activity was carried out from November 18 to December 18, 2023. The "Healthy Sports" activity program is carried out every Sunday morning with the children of Pangkalan Village. The results of this activity are, the residents are aware of the importance of exercising regularly. healthy sports activities "leisurely walk" runs well. The residents are very enthusiastic about welcoming the healthy sports program "leisurely walk".